Connecting to nature in pre-school - Guimarães Gabriel, Amanda (2021)
Outdoor environments and nature could positively support pre-school children living in lowsocial economic urban environments. By valuing the role of lived experiences, this research explores how outdoor places and nature could support and counteract the widespread inequities that affect these children. While the literature has evidence for the role of nature in children´s development and positive senses of place, it has been argued for the need for studies in different economic and cultural backgrounds, which is addressed by this thesis. The study is a participative, child-centered, empirical, qualitative study that investigates the role of distinct environments in children's agency to use, play and learn and concurrently develop senses of place. Experiences of a group of pre-school children's outdoor environments during pre-school days are explored while assuming the dynamic interrelationship of the physical, social, and organizational characteristics of everyday life related to children's development. The departure is taken in the socioecological framework for human development by Bronfenbrenner, Stokols; Sense of place by Relph and Place-relations literature. This research explores how children attending a pre-school located in a low-social economic area in the south of Sweden create meaning and experience places in their everyday lives, including their schoolyard, their local neighborhood, and occasional excursions to the Landscape Laboratory in SLU Alnarp. This inquiry draws on ethnographic methods: participant observation with fieldnotes, photographs, and workshops in which children would draw favorite places, including informal conversations and a walking interview with children and informal conversations with the school's pedagogues. Following children outdoors on many occasions during autumn 2020 revealed aspects of the environment connected to their use of places. The inductive, qualitative analysis suggested the importance of access to suitable outdoor environments containing nature, giving children the opportunity for free play and adult support in children's development of place meaning. The results explore the underpinned value of outdoor environments and nature whilst relating to the value of the cultivation of positive place relationships in childhood. The result highlighted how natural environments in the schoolyard related to children's agency during active play, social interactions, and self-learning activities. Regular visits to a site with a natural environment with a larger abundance of affordances facilitating usage and play seemed to make an imprint on their play in their schoolyard, with a larger and more creative usage of place. Regular walks in their local neighborhood also supported children's agency to create positive place relations to their local environments. In the results section, a "narrative map" illustrates places in terms of children's meaning-making experiences. A thematic result explored how outdoor environments became places related to children's learning experiences. The discussion suggests implications for environmental planning, pedagogical practices, and organizational efforts to counteract the negative environmental impacts on pre-school children living in low-social economical areas and could be applied in pre-school children in all contexts, supporting their development and learning.